AFLP analysis of relationships among cassava and other Manihot species - Roa, A.C.; Maya, M.M.; Duque E., Myriam Cristina; Tohme, Joseph M.; Allem, A.C.; Bonierbale, Merideth W. (1997)
Despite the worldwide importance of cultivated cassava (M. esculenta Crantz) its origin and taxonomic relationships with other species in the genus have not been clearly established. We evaluated a representative sample of the crop’s diversity and six wild taxa with AFLPs to estimate genetic relationships within the genus. Groupings of accessions of each species by data analysis corresponded largely with their previous taxonomic classifications. A mixed group, consisting of Manihot esculenta subsp. flabellifolia and M. esculenta subsp. peruviana, was most similar to cassava, while M. aesculifolia, M. brachyloba, and M. carthaginensis were more distant. Species-specific markers, which may be useful in germ-plasm classification or introgression studies, were suggested by the unique presence of AFLP products in samples of each of the three wild species. Heterogeneity of similarities among individuals of certain species suggested the existence of intraspecific gene pools, a hypothesis that was supported by morphological or ecogeographic evidence with varying degrees of success. Quantitative assessment of genetic diversity revealed greater homogeneity among cassava accessions than among itsclosest wild relatives. The demonstration of unique genetic diversity in the two M. esculenta subspecies and their genetic similarity to the crop supports the hypothesis that these materials may be the ancestors of cassava.